The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/1558944719855447
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Between Darrach and Sauvé-Kapandji Procedures for Post-Traumatic Distal Radioulnar Joint Dysfunction

Abstract: Background: There are various treatments for post-traumatic distal radioulnar joint (DRUJ) dysfunction. The present study aimed to assess differences in long-term patient-reported outcomes on physical function, pain, and satisfaction between the Darrach and Sauvé-Kapandji procedures. Secondary aims were to describe the radiographic outcomes and to assess the difference in rate and type of complications and reoperations between these 2 procedures. Methods: We retrospectively analyzed 85 patients who had a post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…The complication rate was reported to be 30% and 50% respectively, while the reoperation rate was 18% and 36% respectively. Overall, 52 patients (61%) in this study completed a PROS, and the authors did not find any significant difference in pain and satisfaction rate in between the two groups [ 2 ]. In a recent long-term follow-up study of the Sauve-Kapandji procedure, Nagy et al found a high incidence of revision surgery due to instability to the proximal ulnar stump and recommended a restriction of this method to only very selected cases [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The complication rate was reported to be 30% and 50% respectively, while the reoperation rate was 18% and 36% respectively. Overall, 52 patients (61%) in this study completed a PROS, and the authors did not find any significant difference in pain and satisfaction rate in between the two groups [ 2 ]. In a recent long-term follow-up study of the Sauve-Kapandji procedure, Nagy et al found a high incidence of revision surgery due to instability to the proximal ulnar stump and recommended a restriction of this method to only very selected cases [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…total (Darrach) or partial (Bowers) resection of the ulnar head, and the Sauve-Kapandji procedure [ 1 ]. The resulting condition after these traditional procedures may cause painful impingement between the distal ulnar stump and the radius during manual load [ 2 ] and are commonly used in older individuals with rheumatoid changes [ 3 ]. In the Bowers procedure, sufficient soft tissue surrounding the joint is mandatory in order to avoid stylocarpal impingement, which is a potential complication [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Verhiel et al. [ 15 ] comment that prior trauma and preparation of the DRUJ for fusion may create a stimulus for heterotopic ossification and that it is more likely to occur with incomplete resection of the ulnar periosteum, while there is also mention of an intraperiosteal resection technique [ 16 ], which leaves periosteal tissue in the pseudarthrosis gap. In our case, an intraperiosteal osteotomy was performed during index surgery, of which the remaining periosteum was utilized as interposition material.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, radiologic evidence of ossification was noted 17 months after surgery and progressed precipitously to near complete synostosis within 18 months postoperatively with concomitant loss of pronation and supination. With the distal radioulnar arthrodesis-hardware out of reach of the proximal ulnar stump, the remaining potentially stimulating and modifiable factors at the osteotomy site is limited to soft tissue interposition-, stabilization, or suspension methods previously described by several authors ( Table 1 ) [ 5 , 9 , 10 , 15 , 17 ]. However, according to this literature review, no significant pattern can be elucidated when evaluating for a trend of ossification towards one specific procedure modification.…”
Section: Discussionmentioning
confidence: 99%